Morphological aspects and storage of Dypsis leptocheilos (Hodel) Beentje & J. Dransf. (Arecaceae) seeds - Batista, G. S. [UNESP]; Pimenta, R. S. [UNESP]; Gimenes, R. [UNESP]; Pivetta, K. F.L. [UNESP]; Romani, G. N. [UNESP]; Mazzini, R. B. [UNESP] (International Society for Horticultural Science (ISHS), 2012)
Dypsis leptocheilos (Hodel) Beentje & J. Dransf. palms are widely used in landscaping, however there is a lack of studies about its biology, especially on the morphology of its seedling disseminules and the ideal seed storage time without loss of viability. The objectives of this work were to describe the morphological aspects and to study the storage effect on the germination of D. leptocheilos seeds. The experiments were performed at FCAV/UNESP, Jaboticabal Campus, Sao Paulo State, Brazil. In order to obtain a morphology description 100 disseminules were sowed in vermiculite. The external and internal sides of the disseminules as well as the representative phases of the germination process were sketched with the help of a light chamber attached to a stereomicroscope. Five treatments were arranged in order to study the storage effects on the seeds (four months of storage and straight after harvest), with four replicates with 25 disseminules each (seeds with attached endocarp) in a completely randomized design. The germination test was conducted over a 140 days period and noted every two days. In order to calculate the germination percentage (% G) and the Germination Speed Index (GSI), the seeds were considered germinated when the germinative button appeared. The data were submitted to a polynomial regression analysis to verify the behavior of the variables over the storage period. The D. leptocheilos seeds have rounded shape, ruminate endosperm and hard consistency. The embryo is lateral, peripheral and relatively undifferentiated, with approximately 3 mm long and conical shape. The germination percentage increased from 17% for seeds sowed straight after harvest to 73% for those stored over a three-month period. For the GSI the increase was about 0.85%. It was concluded that the germination of D. leptocheilos is of an adjacent ligulate type. Furthermore, the seeds stored for 3 months at 14°C showed both higher percentage and germination speed.
Keywords: Disseminules; Palm; Seedling